The Effect Of Entrepreneurship Education, Self-Efficiency, and Gender On Entrepreneurship Intention Through Entrepreneurship Attitude ( Study in Management Study Program Students, Faculty of Economics Universitas Negeri Makassar) - Deddy Ibrahim Rauf; Heri Pratikto; Agung Winarno (CV. AFDIFAL MAJU BERKAH, 2022)
The highest unemployment rate is caused by the educated group which is a phenomenon of the low interest in entrepreneurship among Indonesian youth which is a problem. The way to overcome unemployment is to increase interest in entrepreneurship. The fact shows that students who have attended entrepreneurship education will provide the development of entrepreneurial intentions that need to be learned. This study is to investigate the entrepreneurial intention of the students of the Faculty of Economics and Business, State University of Malang that the entrepreneurial intention is a factor by using the variables of entrepreneurship education, self-efficacy, gender, and entrepreneurial attitude variables as a mediation. Descriptive quantitative research using SPSS. Entrepreneurial intention variable (Y), independent variable is entrepreneurship education (X1), self-efficacy (X2) and gender (X3) while the mediating variable is entrepreneurial attitude (Z). The results of this study indicate that (1) entrepreneurship education on entrepreneurial intentions has a significant influence, (2) self-efficacy on entrepreneurial intentions has a significant influence, (3) gender on entrepreneurial intentions has a significant influence, (4) entrepreneurial education on entrepreneurial intentions Entrepreneurship mediated by entrepreneurial attitudes has a significant effect, (5) self-efficacy on entrepreneurial intentions mediated by entrepreneurial attitudes has a significant influence, (6) gender on entrepreneurial intentions mediated by entrepreneurial attitudes has a significant influence, (7) entrepreneurial attitudes on intentions entrepreneurship has a significant influence.